Photonic nanorods with magnetic responsiveness regulated by lattice defects. Issue 9 (15th February 2017) - Ma, Huiru; Tang, Kai; Luo, Wei; Ma, Lin; Cui, Qian; Li, Wei; Guan, Jianguo
Abstract : Photonic nanorods are magnetically assembled into long, aligned nanochains, resulting in a unique variety of optical properties in a magnetic field. Abstract : Herein, we use experiments and numerical simulations to demonstrate a novel class of magnetically responsive photonic crystals (MRPCs) based on photonic nanorods which exhibit multiple optical properties in a magnetic field ( H ) due to their fixed photonic nanorods and H -tunable lattice defects. As an example, superparamagnetic Fe3 O4 @polyvinyl pyrrolidone (PVP)@SiO2 photonic nanorods were fabricated through a polyacrylic acid-catalysed hydrolysis–condensation reaction of γ-mercaptopropyltrimethoxysilane around chain-like PC templates formed by monodispersed Fe3 O4 @PVP particles under H . For the as-proposed MRPCs, with increasing H, the photonic nanorods firstly experience in situ rotational orientation along the H direction, followed by alignment and connection into long parellel nanochains via the spaces between the ends of adjacent photonic nanorods (named lattice defects). As the number and size of the lattice defects changes with H, the MRPCs exhibit visible red-shifts and blue-shifts of their diffraction wavelengths in addition to monotonous enhancement of their diffraction peaks. These optical properties are very different from those of previously reported MRPCs. The diversity of the structural colors and brightness of these MRPCs with H is also closely dependent on the applied time of H, the concentration of the photonic nanorods, and the structural parameters of the nanorods, including nanorod length and interparticle distance. Due to the difficult duplication of their various optical properties as well as their easy fabrication and low cost, MRPCs based on photonic nanorods are suitable for wide applications in forgery protection and information encryption.